ANALISIS PENGARUH KUALITAS PELAYANAN AKADEMIK TERHADAP LOYALITAS MAHASISWA UNUSIDA DENGAN PENDEKATAN PARTIAL LEAST SQUARE (PLS) - Usada, Untung; Hakim, Luqman; Kurniawati, Anita T. (Universitas Nahdlatul Ulama Sidoarjo, 2016)
University does not only provide graduates in quantity but also concern about the quality and high discipline,capable of being dinamisator, innovator, motivator and agent of change and to thread high quality of human resources for the various types and levels of expertise. University should care to students’ service quality. University of Nahdlatul Ulama Sidoarjo is a new university in Sidoarjo. This University insists to improve the service quality. Service improvement is expected to affect the students’ satisfaction and trust. So it will be impected on students’ loyalty. The purpose of this study is to identify the impact of satisfaction level of service quality and trust which are expected to affect the students’ loyalty. The method used in this study is Partial Least Square (PLS), Smart PLS 2.0. The analysis results of existing models shows that service quality has an important role in keeping the students’ loyalty. For students, excellent service will give satisfaction and trust so the loyalty can be risen.